Spatial Calibration for the Inertial Measurement Unit - Avrutov, Vadym (International Journal of Sensors Wireless Communications and Control, 2017)
Background: A new calibration method for Inertial Measurement Unit (IMU) of Strapdown Inertial Navigation Systems was presented. IMU consists of inertial sensors like accelerometers, gyroscopes and a circuit of signal processing. Normally, a rate transfer test and multi-position tests are used for IMU calibration. In fact, it suggests turning over IMU around three axes simultaneously. In order to solve the equation of calibration, it is necessary to provide an equality of a rank of basic matrix into degree of basic matrix. For convenient or mechanical gyroscopes with g – and g2 – drifts, it is proposed as a way of problem solving. Method: The new calibration method is based on the whole angle rotation or finite rotation. Results: The results of simulated IMU data presented to demonstrate the performance of the new calibration method. Conclusion: In this paper, a new calibration method was suggested for IMU of strapdown inertial technology. The new calibration method is based on whole angle rotation. The proposed method can provide more real environment conditions when IMU turns around three axes simultaneously in comparison to traditional calibrations when IMU is rotated around one sensitive axis at each time. Besides, the new method has saved a testing time at three times at least.
Keywords: output signals